In Vitro-Generated Tc17 Cells Present a Memory Phenotype and Serve As a Reservoir of Tc1 Cells In Vivo - Flores-Santibáñez, Felipe; Cuadra, Bárbara; Fernández, Dominique; Rosemblatt, Mariana V.; Núñez, Sarah; Cruz, Pablo; Gálvez-Cancino, Felipe; Cárdenas, J. César; Lladser, Alvaro; Rosemblatt, Mario; Bono, María Rosa; Sauma, Daniela (Frontiers in Immunology, 2018)
Memory CD8+ T cells are ideal candidates for cancer immunotherapy because they can mediate long-term protection against tumors. However, the therapeutic potential of different in vitro-generated CD8+ T cell effector subsets to persist and become memory cells has not been fully characterized. Type 1 CD8+ T (Tc1) cells produce interferon (IFN)-γ and are endowed with high cytotoxic capacity, whereas IL-17-producing CD8+ T (Tc17) cells are less cytotoxic but display enhanced self-renewal capacity. We sought to evaluate the functional properties of in vitro-generated Tc17 cells and elucidate their potential to become long lasting memory cells. Our results show that in vitro-generated Tc17 cells display a greater in vivo persistence and expansion in response to secondary antigen stimulation compared to Tc1 cells. When transferred into recipient mice, Tc17 cells persist in secondary lymphoid organs, present a recirculation behavior consistent with central memory T cells and can shift to a Tc1 phenotype. Accordingly, Tc17 cells are endowed with a higher mitochondrial spare respiratory capacity than Tc1 cells and express higher levels of memory-related molecules than Tc1 cells. Together these results demonstrate that in vitro-generated Tc17 cells acquire a central memory program and provide a lasting reservoir of Tc1 cells in vivo, thus supporting the use of Tc17 lymphocytes in the design of novel and more effective therapies.